Achieving on-Time IT Project Delivery in an Indonesian Car Manufacturer (Architecture Image Studies, 2025)
To stay ahead of competition in the Indonesian market, one of the car manufacturers in Indonesia commits to digitalization by improving project management in IT projects. This improvement is needed due to the increasing number of IT projects with IT project delays between 2021 and 2024, which is hindering the Corporate Information Technology (CIT) division from achieving its KPI of 80% on-time project delivery. To address this issue, CIT needs to understand their current project management maturity level by conducting a CMMI level 2 assessment using the SCAMPI method. The output of this assessment is the score of each process area in CMMI level 2. After understanding which process area that still not yet passed the settled passing rate, CIT can further analyze which process area in CMMI level 2 to prioritize for improvement by using Pareto analysis. Finally, after getting Pareto of each process area in CMMI level 2, authors will give recommendations on each process area based on the previous study and analysis. This research will help the corresponding company and related fields on how to improve IT project management using CMMI level 2, SCAMPI and Pareto analysis.